2006
DOI: 10.1038/nrm1909
|View full text |Cite
|
Sign up to set email alerts
|

At the heart of the chromosome: SMC proteins in action

Abstract: Structural maintenance of chromosomes (SMC) proteins are ubiquitous in organisms from bacteria to humans, and function as core components of the condensin and cohesin complexes in eukaryotes. SMC proteins adopt a V-shaped structure with two long arms, each of which has an ATP-binding head domain at the distal end. It is important to understand how these uniquely designed protein machines interact with DNA strands and how such interactions are modulated by the ATP-binding and -hydrolysis cycle. An emerging idea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
487
1
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 487 publications
(496 citation statements)
references
References 82 publications
5
487
1
1
Order By: Relevance
“…It contains four subunits, Smc1, Smc3, Rad21, and Stromalin (SA), which form a ring-like structure (reviewed in Hirano 2006;Huang et al 2005;Losada 2007;Nasmyth and Haering 2005). In most organisms, cohesin is loaded along chromosomes during telophase and is removed from the arms at the subsequent prophase.…”
Section: Introductionmentioning
confidence: 99%
“…It contains four subunits, Smc1, Smc3, Rad21, and Stromalin (SA), which form a ring-like structure (reviewed in Hirano 2006;Huang et al 2005;Losada 2007;Nasmyth and Haering 2005). In most organisms, cohesin is loaded along chromosomes during telophase and is removed from the arms at the subsequent prophase.…”
Section: Introductionmentioning
confidence: 99%
“…Cohesin consists of a heterodimer of the Smc1 and Smc3 structural maintenance of chromosome proteins, and two other proteins, the α-kleisin Rad21 (Mcd1/Scc1) and Stromalin (SA/Scc3; reviewed in Hirano 2006;Nasmyth and Haering 2005). The Rad21 termini interact with the head domains of Smc1 and Smc3, forming a ringlike structure.…”
Section: Introductionmentioning
confidence: 99%
“…Its ring-like structure is the basis of the current cohesion models, in which cohesin encircles two sister chromatids or cohesin rings bound to two sisters interlock with each other (Hirano 2006;Huang et al 2005;Losada 2007;Nasmyth and Haering 2005). In some cases, a cohesin ring that encircles one sister may interact with proteins bound to the other sister to establish cohesion (Chang et al 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 SMCHD1 is an atypical member of the SMC gene superfamily, a family of proteins which is involved in chromosome condensation and cohesion, genome maintenance and gene regulation. [17][18][19] Chromatin immunoprecipitation studies showed the presence of SMCHD1 on the D4Z4 array and its reduced binding to D4Z4 in SMCHD1 mutation carriers. 14 SMCHD1 variants can also modify the disease severity in FSHD1 families, explaining some of the clinical variability seen in FSHD.…”
Section: Introductionmentioning
confidence: 99%